Preparation, Characterization And Application Of Lignin Graft Copolymer As A Drilling Mud Additive - Haras, Mohamed-Rashid Ahmed Mohamed Haras (2010)
Water soluble lignin graft copolymer (LGC) was prepared from oil palm empty fruit bunch (OPEFB) fiber as a renewable biomass source. Beforehand, Kraft lignin (KL) was extracted by exploiting the OPEFB fiber Kraft pulping residue. The KL extraction was accomplished through the acid precipitation of black liquor which was obtained from the Kraft pulping process. KL was then grafted with acrylic acid (AA) by using p-toluenesulfonic acid (PTS) as a catalyst in the condensation process via bulk technique. The resulting copolymer was characterized by Fourier transform infrared (FTIR) spectroscopy, differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA). The FTIR spectrum of the product showed absorption due to the presence of ester bonds as a proof of grafting.